2018
DOI: 10.3906/elk-1710-128
|View full text |Cite
|
Sign up to set email alerts
|

User interaction in hands-free gaming: a comparative study of gaze-voice and touchscreen interface control

Abstract: The goal of the present study is to contribute to the research on the use of eye tracking in hands-free gaming.We report the results of an experimental study by using a platform game designed by the authors. The game allowed gaze-voice command control, as well touchscreen control of the interface by the player. We employed a set of performance measures and we measured player engagement as an indicator of user experience. The findings revealed that the players did not improve in game performance when they used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Since has a capacity to carry rich information from a human to a machine, making it to play such an oversimplified role can be perceived as counterintuitive and boring, especially to healthy users. This could be one of the reasons why in all previous attempts to combine voice and gaze in a hybrid human-machine interface, more complex voice commands were explored [12][13][14][15][16][17][18][19][20]. However, the participants of our study successfully fulfilled multiple selections on a computer screen using the simple "voice-as-click" approach, only slightly slower than with mouse-click confirmation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since has a capacity to carry rich information from a human to a machine, making it to play such an oversimplified role can be perceived as counterintuitive and boring, especially to healthy users. This could be one of the reasons why in all previous attempts to combine voice and gaze in a hybrid human-machine interface, more complex voice commands were explored [12][13][14][15][16][17][18][19][20]. However, the participants of our study successfully fulfilled multiple selections on a computer screen using the simple "voice-as-click" approach, only slightly slower than with mouse-click confirmation.…”
Section: Discussionmentioning
confidence: 89%
“…The gaze is often used together with a voice in natural communication, e.g., in joint attention [9], in turn-taking [10], and in direct gaze interaction [11]. Attempts were made to combine gaze-and voice-based interaction in a single technology [12][13][14][15][16][17][18][19][20]. Indeed, it seems natural to use voice communication as a most natural and information-rich channel, and to supplement it with gaze pointing whenever spatial information is helpful, e.g., to quickly indicate where or on which object an action should be applied [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their worse game performance in gaze-voice control, their participants reported a higher level of immersion for gaze-voice control compared to keyboard-mouse control. Uludagli and Acarturk [37] conducted a comparative study of gaze-voice and touchscreen interface control. They found that the participants exhibited higher game performance when they used the touchscreen control and that participants who used the gaze-voice control method were more psychologically absorbed.…”
Section: Eye Gaze and Voice In Computer Gamesmentioning
confidence: 99%
“…Similarly, van der Kemp and Sundstedt proposed a drawing system controlled by voice and gaze, opening new possibilities for creative expression and giving the wider user population access to this kind of application [57]. Further, researchers have combined gaze and voice-based interactions to enhance the immersive experience of players in games [43,56]. In line with previous work, we recognise the benefit of combining these modalities and present a voice note-taking system which combines the natural behaviour of gaze while reading with the convenience and expressiveness of voice for annotating text.…”
Section: Gaze and Voice-based Interactionmentioning
confidence: 99%